Kemampuan Membaca Pemahaman Cerita Pendek Siswa Kelas VIII SMP Negeri 10 Kupang - Bahan, Desi Erna; Margareta, Karus; Nurhuda, Aris (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2025)
This research aims to describe the reading comprehension ability of Class VIII Students of SMP Negeri 10 Kupang. The focus of this research is to measure the extent to which students can understand the intrinsic elements of short stories such as theme, characters, setting, plot and moral messages contained in the text. The research method used is descriptive qualitative, with data collection through reading students' understanding and giving written tests. The research results show that the majority of students are in the capable category in terms of reading with a percentage of 75%, while students who are in the underprivileged category have a percentage of 25%. Factors that influence reading comprehension abilities include interest in reading, availability of appropriate reading materials, and the teaching methods applied by the teacher. Based on these findings, it is recommended that teachers further optimize learning strategies that are interactive and fun, as well as providing reading materials that are relevant to students' interests. It is hoped that the results of this research can be a reference in improving students' reading comprehension skills at SMP Negeri 10 Kupang